Pengembangan Profesional Perawat Rumah Sakit Umum Daerah - Nur Hidayat; Asniar Asniar; Teuku Tahlil (Universitas Faletehan, 2022)
Nursing professional development in health service setting is the main element for improving service quality and nurse satisfaction in doing their main job. It can also prevent nurse burnout and turnover in a health care institution. The purpose of this study was to determine the determinants of nursing professional development at regional general hospitals. The research method used a cross-sectional approach. The sampling used proportionate stratified random sampling with a total sample of 140 nurses. The data was collected by using Questionnaire-Professional Development for Nurses (Q-PDN), Individual Career Management (ICM) questionnaire and Organizational Career Management (OCM) questionnaire. The data analysis used Spearman's rho and multiple logistic regression test. The result showed the majority of individual career management in low category (52.1%), the majority of organizational career management in low category (52.1%), and the majority of nursing professional development in low category (53.6%). The results of the statistical tests showed that there was a significant relationship of individual career management (p=0.000) and organizational career management (p = 0.001) with nursing professional development. The results of multiple logistic regression tests showed that the most significant influencing factor on nursing professional development was individual career management (p=0.003; Exp B=3.039). Debriefing through education and training for nurses is important to do for nursing professional development.